2020
DOI: 10.17263/jlls.712691
|View full text |Cite
|
Sign up to set email alerts
|

How does “to what gender and status one talks” govern the speaker’s strategy in keeping on their conversation?

Abstract: To what gender and status one talks" governs more the speaker, in deciding their culturally and socially accepted strategy in conversation, than "who talks"; as the airport runway dictates the pilot's landing strategy. This paper, employing conversational analysis, tries to explore how the gender and social status of the audience dictate the speaker's speech acts and moves in Muslim formal conversation in three functional topical units composed of 107 acts of directive, assertive, commisive, expressive, rogati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Baker (2013) further says that, in general, the word 'women' is not considered as mature as the word 'men'. In the literature, we find many studies such as Giyoto et al (2020) and Ang (2003); that have investigated the use of speech acts of refusal by different genders in different languages. However, we (the researchers) did not find even a single study that has investigated the gender-based difference in the use of speech acts of refusal in the Khowar language.…”
Section: Introductionmentioning
confidence: 99%
“…Baker (2013) further says that, in general, the word 'women' is not considered as mature as the word 'men'. In the literature, we find many studies such as Giyoto et al (2020) and Ang (2003); that have investigated the use of speech acts of refusal by different genders in different languages. However, we (the researchers) did not find even a single study that has investigated the gender-based difference in the use of speech acts of refusal in the Khowar language.…”
Section: Introductionmentioning
confidence: 99%
“…This research supports the idea that effective communication accommodation practices can enhance the overall service experience for customers, especially in diverse cultural environments (Riandy F, 2016). Additionally, research on CAT has shown that accommodation strategies are widely applicable across various situations and contexts see also the research by (Giyoto et al, 2020) emphasize the communication on the interlocutors. So, the adjustment of communication is no longer on the verbal merely, but we have to consider the participants that involve in the conversation.…”
Section: Axiom 3 Gp and The Types Of Accommodationmentioning
confidence: 99%
“…The representation is the way that Jokowi describes the socio-political condition in Indonesia. In addition, speech is a discourse that reflects a certain ideology and forms social cognition, which is the relationship between discourse and Ideology (Fairclough, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%